2016
DOI: 10.1177/1748006x15623869
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive support vector regression method for structural system reliability assessment and its application to a cable-stayed bridge

Abstract: Engineering structures are most statically indeterminate structures consisting of various types of components and their failure modes exhibit randomness under random loads. A new adaptive support vector regression method is proposed for structural system reliability assessment. Compared with traditional support vector regression, the proposed adaptive support vector regression method involves two updating procedures to estimate structural limit state functions. Three verification examples involving a nonlinear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Modeling the ambient influence on the structural health indicators is crucial for reliable structural health monitoring (Brownjohn, 2007; Giagopoulos et al., 2019; Kuok & Yuen, 2012; Li, Yi, Ren, Li, & Huo, 2014; Liu, Lu, Yin, & Noori, 2016; Mu, Yuen, & Kuok, 2016). Due to the nature of complex and volatile mechanism, constructing a representative parametric input–output relationship to describe the subtle environmental effects on materials properties and structural behavior under severe wind loading can be a nontrivial task (Catbas, Susoy, & Frangopol, 2008; Kuok & Yuen, 2016; Lam, Zhang, Ni, & Hu, 2017; Lei, Su, & Shen, 2013).…”
Section: Case Studymentioning
confidence: 99%
“…Modeling the ambient influence on the structural health indicators is crucial for reliable structural health monitoring (Brownjohn, 2007; Giagopoulos et al., 2019; Kuok & Yuen, 2012; Li, Yi, Ren, Li, & Huo, 2014; Liu, Lu, Yin, & Noori, 2016; Mu, Yuen, & Kuok, 2016). Due to the nature of complex and volatile mechanism, constructing a representative parametric input–output relationship to describe the subtle environmental effects on materials properties and structural behavior under severe wind loading can be a nontrivial task (Catbas, Susoy, & Frangopol, 2008; Kuok & Yuen, 2016; Lam, Zhang, Ni, & Hu, 2017; Lei, Su, & Shen, 2013).…”
Section: Case Studymentioning
confidence: 99%
“…Wang et al [31] proposed a semi-analytical method to assess the system reliability of a series bridge network subjected to non-stationary loads and investigated the sensitivity of system reliability to the load intensity, number of components and resistance correlation. Liu et al [32] proposed an adaptive support vector regression method for system reliability assessment and utilized a prestressed concrete (PC) cable-stayed bridge to verify the applicability of this method. Significant researches have been devoted to reliability evaluation of complex bridge system.…”
Section: Introductionmentioning
confidence: 99%
“…From the investigation of the reliability by Liu et al, 20 Vapnik 21 and Li et al, 22 it is found that the application of SVM in reliability analysis needs to be researched deeply. In order to estimate the reliability of implicit performance function that encountered in structural safety assessment, in this article, the non-probabilistic reliability index of the bridge crane metal structure system is derived by convex model, and then, the sample of the stress and uncertainty parameters of the structural danger point can be obtained by experiment.…”
Section: Introductionmentioning
confidence: 99%